PEMBENTUKAN KARAKTER RELIGIUS PADA SISWA TUNAGRAHITA DI SPKH (SEKOLAH PENDIDIKAN KHUSUS) NEGERI KARANGANYAR - Devi Yaniar Wi Hargina (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
This study aims to determine how the process of forming religious character for students with mental retardation at SPKH Negeri Karanganyar, Kebumen Regency. This research uses qualitative research methods, using interview and observation instruments. This research was conducted on 6 children with mental retardation in class X C at SPKH Negeri 1 Karanganyar. The results of the analysis include how the process of character building for students with mental retardation, the efforts made in the formation of religious characters for students, as well as the challenges of character formation faced from the pre-pandemic to post Covid-19 pandemic